A spectroscopic study of the composition and conformation of cholesteryl and wax esters purified from meibum. (August 2021) - Ewurum, Anthony; Ankem, Akhila; Georgiev, Georgi; Borchman, Douglas
Highlights: A wax (WE) ester –cholesteryl ester (CE) mixture could be necessary in the tear film lipid layer to form a more stable tear film. WE may be a necessary component of sebum, the cuticle of plants and the exoskeleton coating of insects which fluidize pure CE allowing the mixture to spread. A more fluid CE (relative to WE) would have a more profound effect on the conformation of native WE-CE mixtures composed only of WE. A more fluid CE, (relative to WE) would stabilize the tear film lipid layer compared with a tear film lipid layer composed of just WE or CE or alone. The nature of hydrocarbon chain conformation and packing of a CE-WE mixture depends on the conformation of the WE and CE. Abstract: Elucidating wax ester (WE) and cholesteryl ester (CE) compositional, structural and functional relationships is key to our understanding of how these lipids are involved in natural and pathological processes. Little is known about how CE and WE interact with one another. The focus of the present study is to bridge this gap of knowledge. CE and WE were collected from human meibum as a source of esters with complex hydrocarbon chains. MgO column chromatography was used to separate WE and CE. The esters were characterized using 1 H-NMR and Fourier transform infrared spectroscopy. The complexity of the hydrocarbon chains of native WE and CE influenced how changes in the ratio of WE and CE ester influenced some lipid phase transitional parameters but not others. Changes in CE content of WE/CE mixtures undoubtedly modifies the hydrocarbon chain conformation and packing of the mixture. The nature of the change depends on the conformation of the WE and CE. Differences in the complexity of the hydrocarbon chains are likely not to be a major influence on alterations in the order or phase transition temperature when more ordered WE is added to less ordered CE.